2021
DOI: 10.3390/molecules26237311
|View full text |Cite
|
Sign up to set email alerts
|

Constituents from the Fruiting Bodies of Trametes cubensis and Trametes suaveolens in Vietnam and Their Anti-Inflammatory Bioactivity

Abstract: It is reported that various fungi have been used for medicine and edible foods. The tropical Trametes genus is popular and well-known in Vietnam for its health effects and bioactivities. In this study, the fruiting bodies of the edible fungi T. cubensis and T. suaveolens were collected in Vietnam. The preliminary bioactivity screening data indicated that the methanol extracts of the fruiting bodies of T. cubensis and T. suaveolens displayed significant inhibition of superoxide anion generation and elastase rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…memiliki potensi dalam bidang farmasi. Hal ini disebabkan beberapa spesies Trametes memiliki aktivitas bioaktif sebagai antimikrob (Bains dan Chawla 2020) dan antiinflamasi (Li et al 2021). Trametes sp.…”
Section: Marasmius Haematocephalusunclassified
“…memiliki potensi dalam bidang farmasi. Hal ini disebabkan beberapa spesies Trametes memiliki aktivitas bioaktif sebagai antimikrob (Bains dan Chawla 2020) dan antiinflamasi (Li et al 2021). Trametes sp.…”
Section: Marasmius Haematocephalusunclassified
“…The most important bioactive fungal proteins include lectins (glycoproteins) that contribute to lowering blood sugar levels, immunomodulatory proteins, and proteins with enzymatic activity such as laccase (Łysakowska et al 2023). In addition, it consists of special compounds called hepatocellular found in T. versicolor mushroom Li et al (2021), which activate the immune system and show chemo-preventive effects against various types of cancer (Rizki and Tamai 2011). The highest protein content (14.65%) in this study is higher compared to the ndings of Kıvrak et al (2020), who reported the crude protein content of T. versicolor mushroom to be 11.07%.…”
Section: Nutritional Composition Of T Versicular Mushroommentioning
confidence: 99%